Hutan Adat dalam Perspektif Islam: Studi Kasus Hutan Adat Guguk Propinsi Jambi - Devrian Ali Putra (JURNAL INDO-ISLAMIKA, 2015)
The article concludes that the preservation of environment better prevails when is prevails when is applied Islamic based customary law. The strict implementation of the Islamic based customary law will lead healthier environment. The customary forest based on this law would be the best religious practices deals with the environmental crisis. This forest would be resilient against the damage on the protection and preservation of Islamic based customary law. Moreover, this should be supported by religious, social-political, and educational values.